The Impact Of Current Reforms On Income Distribution In Peru: Additional aspects - Peñaranda C., César (1974)
The purpose of the present article is to discuss the work of Adolfo Figueroa about income distribution in Peru. It pretends to extend the approach on the previous history of the Peruvian economy, to have a broader vision of the frame where different reforms were made, as well as the reasons behind them.